Physiological Aspects of Seed Source Variation in Seed Germination of Quercus leucotrichophora A. Camus - Nautiyal, A. R.; Rawat, D. C. S.; Prasad, Pankaj (Indian Forester, 2000)
Seeds of Q. leucotrichophora A. Camus were collected from seven places in Garhwal and Kumaun regions varying considerably in their longitude, latitude and altitude and tested for their seed attributes, germinability, seedling growth and survival. Provenances differed from each other in mean seed weight, germinability of seeds and seedling growth. However, differences were significant more in rate of germination than total germination percentage. Didihat seed source gave best results over all other seed sources.